Global Phosphoproteomics Analysis of IBRS-2 Cells Infected With Senecavirus A - Jieyi Li; Zhongwang Zhang; Zhongwang Zhang; Jianliang Lv; Jianliang Lv; Zhongyuan Ma; Li Pan; Li Pan; Yongguang Zhang; Yongguang Zhang (Frontiers in Microbiology, 2022)
Phosphorylation is a widespread posttranslational modification that regulates numerous biological processes. Viruses can alter the physiological activities of host cells to promote virus particle replication, and manipulating phosphorylation is one of the mechanisms. Senecavirus A (SVA) is the causative agent of porcine idiopathic vesicular disease. Although numerous studies on SVA have been performed, comprehensive phosphoproteomics analysis of SVA infection is lacking. The present study performed a quantitative mass spectrometry-based phosphoproteomics survey of SVA infection in Instituto Biologico-Rim Suino-2 (IBRS-2) cells. Three parallel experiments were performed, and 4,520 phosphosites were quantified on 2,084 proteins. Gene Ontology (GO) functional enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses showed that many phosphorylated proteins were involved in apoptosis and spliceosome pathways, and subcellular structure localization analysis revealed that more than half were located in the nucleus. Motif analysis of proteins with differentially regulated phosphosites showed that proline, aspartic acid, and glutamic acid were the most abundant residues in the serine motif, while proline and arginine were the most abundant in the threonine motif. Forty phosphosites on 27 proteins were validated by parallel reaction monitoring (PRM) phosphoproteomics, and 30 phosphosites in 21 proteins were verified. Nine proteins with significantly altered phosphosites were further discussed, and eight [SRRM2, CDK13, DDX20, DDX21, BAD, ELAVL1, PDZ-binding kinase (PBK), and STAT3] may play a role in SVA infection. Finally, kinase activity prediction showed 10 kinases’ activity was reversed following SVA infection. It is the first phosphoproteomics analysis of SVA infection of IBRS-2 cells, and the results greatly expand our knowledge of SVA infection. The findings provide a basis for studying the interactions of other picornaviruses and their mammalian host cells.